1990
DOI: 10.2331/suisan.56.1331
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification and characterization of phospholipase A2 from the hepatopancreas of red sea bream.

Abstract: Although apparent phospholipase A2 activity is very low in freshly prepared hepatopancreas homogenates of red sea bream, its activity increased considerably during autolysis.Hence, phospholipase A2 was purified about 14,500-fold from the dialyzate of delipidated powder of frozen hepatopancreas homogenate by the sequential use of column chromatographies on DEAE-sepharose CL-6B, Toyopearl HW-55F, reversed phase HPLC, and TSK-GEL G3000SW.The final enzyme preparation was nearly homogeneous in SDS-polyacrylamide ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
3

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 10 publications
2
43
0
3
Order By: Relevance
“…The differential lipase response was explained as being possibly caused by differences in the FA composition of the diet, related to the specificity of lipase towards FA differing in chain length and degree of saturation. The method utilized in the present experiment is most likely determining the activity of the non-specific bile saltactivated lipase which has been shown to have a higher affinity for PUFA (Iijima et al, 1998;Izquierdo et al, 2000). Nevertheless, as mentioned above, the smaller size of LS larvae must be at least partly responsible for the reduction in segmental lipase activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differential lipase response was explained as being possibly caused by differences in the FA composition of the diet, related to the specificity of lipase towards FA differing in chain length and degree of saturation. The method utilized in the present experiment is most likely determining the activity of the non-specific bile saltactivated lipase which has been shown to have a higher affinity for PUFA (Iijima et al, 1998;Izquierdo et al, 2000). Nevertheless, as mentioned above, the smaller size of LS larvae must be at least partly responsible for the reduction in segmental lipase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Trypsin activity was assayed using BAPNA (Na-benzoyl-DL-argininep-nitroanilide) (Sigma-Aldrich) as substrate (Tseng et al, 1982), while the activity of alkaline phosphatase was measured following the method of Bessey et al (1946), using as subtrate p-nitrophenylphosphate (pNPP) (Sigma-Aldrich). Lipase activity was assayed according to a spectrophotometric method slightly modified from Iijima et al (1998), using as substrate pnitrophenyl myristate (Sigma-Aldrich) (Morais et al, 2004a). Enzyme specific activities were expressed as μmoles of substrate hydrolyzed per minute, per mg of protein (i.e., U mg protein − 1 ) at 25°C for trypsin, 37°C for alkaline phosphatase and 30°C for lipase.…”
Section: Enzyme Analysismentioning
confidence: 99%
“…Although it was impossible to measure the activities of PLase A in plankton because of a shortage of samples for assay, the phenomena of enhancement in FF A release by Ca + + in both plankton (at pH 9) and oysters (at pH 7) suggest that PLase A2 might be enhanced by addition of Ca + + as well as PLase A2 in mammalian cells 9 ) and in the hepatopancreas of fish. 10) On the other hand, the responses of additives such as ions and chelates to PC metabolites in oysters differed between pH 4 and 7, which indicated that PLase A in oysters might be derived from at least two kinds of cell organelles. Nalbone et al 7) reported that lysosomal PLase A in rat heart was not influenced by the addition of Ca + + and EDT A. Judging from the data already reported, 11) PLase A, which is activated at pH 4, would originate from lysosomes.…”
Section: Methodsmentioning
confidence: 99%
“…Λιγότερες αναφορές υπάρχουν για την ενεργότητά της λιπάσης στους ιχθύς, αλλά έχει παρατηρηθεί ότι τα σαρκοφάγο έχουν υψηλότερη ενεργότητά λιπάσης από τα φυτοφάγα και τα παμφάγα (Chakrabarti, 1995, Opuzynski, 1995, Tengjaroenku, 2000. Τα διαιτητικά λιπίδια παίζουν σημαντικό ρόλο ως πηγή ενέργειας για τα σαρκοφάγο είδη όπου η διαθεσιμότητα των υδατανθράκων για ενέργεια είναι χαμηλή (Iijima, 1998).…”
Section: πεπτικότητα υδατανθράκωνunclassified
“…Αντιθέτως, η υψηλότερη τιμή ενεργότητας της μαλτάσης παρατηρήθηκε στα πυλωρικά τυφλά στο Ασιατικό λαυράκι (Lates calcarifer) (Harpaz et al, 2005) Στο πεπτικό σύστημα διαφόρων ειδών ιχθύων έχουν ανιχνευτεί διάφορες λιπάσες, η φωσφολιπάση Α2, η παγκρεατική λιπάση και η μη ειδική λιπάση που ενεργοποιείται από τα χολικά άλατα (BAL) (Iijima et al, 1998, Izquierdo et al, 2000, Perez-Casanova et al, 2004. Η παρουσία τους είναι αυξημένη στα σαρκοφάγα σε σύγκριση με τα φυτοφάγα ή τα παμφάγα είδη, καθώς τα πρώτα καταναλώνουν τροφές πλούσιες σε λιπαρά (Chakrabarti et al, 1995, Tengjaroenkul et al, 2000.…”
Section: • εντερικό περιεχόμενοunclassified